Relationship between Physical Environment and Smoking Behaviour with Accute Respiratory Infection in Class-I Correctional Institutions in Lowokwaru, Malang - Laily Trisnaningdyah, Devia; ., Supriyadi; Al-Irsyad, Muhammad (KnE Life Sciences, 2021)
Many prisoners experience Accute Respiratory Infection (ARI), and as many as 5,000 new cases are reported every year. This is generally caused by the prisoners’ inadequate physical environment and smoking behaviour. This observational analytical study was conducted using a cross-sectional design over a duration of two months, from December 2019 to January 2020. The independent variables in this study included occupancy density, ventilation, temperature, humidity, lighting and prisoners’ smoking behaviour on a nominal scale, while the dependent variable included the incidence of ARI with a nominal scale. A total of 96 prisoners who were positive for ARI and visited the Class-1 Prison Clinic of Lowokwaru, Malang were selected using the sampling estimation method. While a univariate analysis was used to explain the characteristics of each variable in the study, a bivariate analysis was done to determine the relationship between the independent and dependent variables using the contingency coefficient test. The results of the study indicated that there was a significant relationship between the occupancy density, ventilation, temperature, humidity and lighting, and the incidence of ARI, but no significant relationship was noted between the prisoners’ smoking behaviour and the incidence of ARI in Class-1 prisons of Lowokwaru, Malang. Keywords: physical environment, smoking behaviour, ARI